1985
DOI: 10.1111/j.1432-1033.1985.tb08906.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraparticulate localization and some properties of a clofibrate-induced peroxisomal aldehyde dehydrogenase from rat liver

Abstract: A study was made of the effect of chronic administration of the hypolipidemic drug clofibrate on the activity and intracellular localization of rat liver aldehyde dehydrogenase. The enzyme was assayed using several aliphatic and aromatic aldehydes. Clofibrate treatment caused a 1.5 to 2.3-fold increase in the liver specific aldehyde dehydrogenase activity. The induced enzyme has a high K , for acetaldehyde and was found to be located in peroxisomes and microsomes. Clofibrate did not alter the enzyme activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Precise expression studies of the two human variants will have to elucidate the putative role of FALDH in α-oxidation. Some reports in the literature indicate that a distinct aldehyde dehydrogenase inducible by clofibrate is present in rat liver peroxisomes [52]. However, since it is known that FALDH is also induced by clofibrate [53] and since the aldehyde dehydrogenase that was described by Antonenkov et al [52] is also membrane-bound, it cannot be excluded that microsomal contamination is at the basis of these results.…”
Section: Dehydrogenation Of Pristanal To Pristanic Acidmentioning
confidence: 87%
“…Precise expression studies of the two human variants will have to elucidate the putative role of FALDH in α-oxidation. Some reports in the literature indicate that a distinct aldehyde dehydrogenase inducible by clofibrate is present in rat liver peroxisomes [52]. However, since it is known that FALDH is also induced by clofibrate [53] and since the aldehyde dehydrogenase that was described by Antonenkov et al [52] is also membrane-bound, it cannot be excluded that microsomal contamination is at the basis of these results.…”
Section: Dehydrogenation Of Pristanal To Pristanic Acidmentioning
confidence: 87%
“…Perhaps one candidate protein that could be investigated in future studies is aldehyde dehydrogenase, since Antonenkov and other workers have observed a 2-3 induction of this enzyme in the livers of peroxisome proliferator-treated rats [65,66]. Since certain aldehyde dehydrogenase isoforms can metabolize toxic lipid-derived aldehydes, enhanced activity of this pathway could feasibly provide cellular protection during times of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been claimed that DHAP is synthesized endogenously from glycerol-3-phosphate (G3P) as catalyzed by the enzyme glycerol-3-phosphate dehydrogenase (G3PDH/GPD1). Interestingly, earlier work from Antonenkov (Antonenkov et al, 1985) has shown that rat liver peroxisomes do contain G3PDH activity although the true identity of this enzyme activity has never been resolved definitively. In this respect it is important to mention the work of Jung et al in yeast which revealed dynamic changes in the subcellular distribution of G3PDH ranging from peroxisomal to cytosolic depending on the metabolic status of the cells (Jung et al, 2010).…”
Section: Etherphospholipid Biosynthesis and The Interplay With Other mentioning
confidence: 99%